2022
DOI: 10.30909/vol.05.02.451467
|View full text |Cite
|
Sign up to set email alerts
|

Design, implementation, and insights from a volcanology Virtual Field Trip to Iceland

Abstract: Virtual field trips (VFTs) are an effective form of geoscience teaching to support or provide alternatives to in-person field trips. We report on the design and implementation of the Iceland VFT aimed at teaching physical volcanology in a third-year undergraduate course. An evaluation exercise administered following the VFT allowed students to reflect on their learning and provided insights into the student experience. Students found the VFT an interesting and motivating learning experience due to the three-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Numerous research studies have explored the use of VLs and related pedagogical strategies in wide range of disciplines and educational programs (Calvert & Hume, 2022;Nagdee et al, 2022;Ray & Srivastava, 2020;Shorey & Ng, 2021;Xue & Crompton, 2022). These include a variety of disciplines including health science and medical education (Silberman et al, 2013;Teles et al, 2020;Wright et al, 2018;Zackoff et al, 2023), engineering (Mohamed et al, 2021), science (Engel et al, 2023;Watson et al, 2022;Zahid Iqbal & Campbell, 2023) psychology and consultancy (Neden, 2020), and art (Yu et al, 2023).…”
Section: Concept Of Virtual Labsmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous research studies have explored the use of VLs and related pedagogical strategies in wide range of disciplines and educational programs (Calvert & Hume, 2022;Nagdee et al, 2022;Ray & Srivastava, 2020;Shorey & Ng, 2021;Xue & Crompton, 2022). These include a variety of disciplines including health science and medical education (Silberman et al, 2013;Teles et al, 2020;Wright et al, 2018;Zackoff et al, 2023), engineering (Mohamed et al, 2021), science (Engel et al, 2023;Watson et al, 2022;Zahid Iqbal & Campbell, 2023) psychology and consultancy (Neden, 2020), and art (Yu et al, 2023).…”
Section: Concept Of Virtual Labsmentioning
confidence: 99%
“…Studies also have shown that the use of virtual learning environments resulted in a reduction of face-to-face class time, which in turn increased the opportunity for independent learning (Bak et al, 2023). Incorporating VLs into subjects such as geology and tourism (Schott & Marshall 2018;Watson et al, 2022), which typically require field trips, can also help reduce transportation and logistical expenses (Jones, 2018). Furthermore, with virtual labs, universities can accommodate a larger number of students simultaneously and offer a broader range of experiments and simulations.…”
Section: Virtual Labs and Sustainabilitymentioning
confidence: 99%
See 3 more Smart Citations